2008
DOI: 10.1080/02841860802183612
|View full text |Cite
|
Sign up to set email alerts
|

Cellular senescence in oral cancer and precancer and treatment implications: A review

Abstract: In the short term, the study of this mechanism may yield valuable data for the management of oral cancer and precancer, for which no effective diagnostic or prognostic markers are yet available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…A pro-senescence approach to cancer therapy is an attractive alternative approach to chemotherapeutic strategies [12]. However, abundant reports indicate that cellular senescence occurs in the pre-malignant stage of oral squamous cell carcinoma (OSCC) but is lost once malignant transformation has occurred [13,14,15,16,17]. In contrast, stress or oncogene-induced senescence (OIS) also reported in OSCC and indicated that OIS and its markers could play a role in OSCC tumor progression [18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…A pro-senescence approach to cancer therapy is an attractive alternative approach to chemotherapeutic strategies [12]. However, abundant reports indicate that cellular senescence occurs in the pre-malignant stage of oral squamous cell carcinoma (OSCC) but is lost once malignant transformation has occurred [13,14,15,16,17]. In contrast, stress or oncogene-induced senescence (OIS) also reported in OSCC and indicated that OIS and its markers could play a role in OSCC tumor progression [18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…As has been suggested, OIS could have a role in the development of pre-malignant lesions, explaining p16 Ink4a overexpression in benign and pre-malignant lesions (Zhang et al, 2006;Campo-Trapero et al, 2008). However, p16 Ink4a should stop proliferation in cells with a properly functioning p16 Ink4a -Rb pathway.…”
Section: Subcellular Location Of P16 Ink4a Overexpressionmentioning
confidence: 95%
“…While there are some limitations on the use of activity assays for this enzyme, this marker can be sensitively detected by histochemical staining in most senescent cells and tissue. In addition to negative regulators of the cell cycle, such as p15 IK4b (p15), p16 INK4a (p16), ARF and p21 Cip1/Waf1 (p21), differentiated embryonic chondrocyte expressed-1 (DEC1) and decoy death receptor-2 (DCR2) have been identified as senescence indicators (24,25). Recently, our group also identified cathepsin D and eukaryotic elongation factor 1 as promising markers for the detection of cellular senescence induced by a variety of treatments (26).…”
Section: Cellular Senescence: a Fundamental Aspect Of Cell Biologymentioning
confidence: 99%